Audit quality and cost of equity capital. (1st January 2014) - Basiruddin, Rohaida; Benyasrisawat, Prawat; Rasid, Siti Zaleha Abdul
The purpose of this research is to examine the relationship between audit quality and cost of equity capital. This research argues that the higher the levels of audit quality, the lower the rate of return required by the investor. The cost of equity capital is measured by the price-earnings growth (PEG) model. Audit quality is measured by proxies, including audit fees, non-audit fees, industry specialist auditors and earnings management. Based on 226 largest companies listed on the London Stock Exchange (FTSE 350) during 2005–2008, findings report a significant relationship between earnings management and the cost of equity capital. The research does not find a relationship between the other three audit quality proxies. The results suggest that among larger firms, earnings management is a major issue. Auditors are mainly expected to deal with earnings management. It is more likely that investors perceive auditing as an important mechanism to detect earnings management in large firms, enhancing the value of financial information.